Improved acid-driven inhibition of effector T cell function by a pHLIP variant-conjugated PD-L1 - Hang Zheng; Mianjing Wang; Junjuan Feng; Yuting Zhang; Haiyan Wu; Min Zhang; He Xiao; Chunxia Qiao; Jing Wang; Longlong Luo; Xinying Li; Jiannan Feng; et al. (Scientific Reports)
Abstract Programmed cell death–ligand 1 (PD-L1)/PD-1 axis is crucial for maintenance of immune homeostasis and its impairment partially accounts for the pathogenesis of inflammatory diseases. Hence, augmenting PD-L1/PD-1 signals represents a novel strategy to prevent destructive inflammation and induce immune tolerance. Recently, we developed a new cargo by conjugating the ectodomain of PD-L1 with pHLIP, a low pH-responding and membrane-inserting peptide, and demonstrated its potent immune-suppressive activity under weakly acidic (pH6.1) conditions in vitro. Herein, we further showed that PD-L1-pHLIP (termed as PD-L1-pHLIPwt) responded well to weakly acidic buffer, but not in nearly neutral pH (pH6.8) solutions. To overcome this obstacle, pHLIPwt was replaced by a variant harboring two mutations (Asp14Gla and Asp25Aad) and PD-L1 ectodomain was conjugated to the N-terminus of pHLIP variant via sulfo-SMCC linker (termed as PD-L1-pHLIPva). PD-L1-pHLIPva potently inhibited T effector function including proliferation, activation as well as proinflammatory cytokine release in nearly neutral pH buffer through PD-L1/PD-1 interaction. The inhibitory function of PD-L1-pHLIPva was attributed to more amounts of PD-L1 anchored on the surface of several types of immune cells compared with PD-L1-pHLIPwt. Given that the niche in the lesions of inflammation is weakly acidic even nearly neutral pH, PD-L1-pHLIPva represents a new arsenal to potentially dampen excessive inflammatory reactions.